2021
DOI: 10.1108/cg-06-2020-0240
|View full text |Cite
|
Sign up to set email alerts
|

On the linkage between CEOs’ statements and CSR reporting: an analysis of visuals and verbal texts

Abstract: Purpose Research on corporate social responsibility (CSR) reporting highlights an increasing lack of transparency in the information reported along with concerns surrounding overall reporting practices. One area that needs exploration is how chief executive officers (CEOs) convey messages in relation to CSR. This paper aims to investigate the linkage between CEO’s statements (words and images) in relation to CSR and the performativity of such communication. Design/methodology/approach The study analysed CEOs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 67 publications
(86 reference statements)
0
10
0
Order By: Relevance
“…Furthermore, another linked limitation of this study concerns the lack of investigation of the internal variables (e.g. strategic governance and operational controls, sustainability control systems, CEOs’ statements or characteristics of the corporate boards), and external variables that can significantly affect the sustainability reporting of firms (Githaiga and Kosgei, 2022; Raimo et al , 2022; Effah et al , 2022; Khan and Sulaiman, 2021; Nursimloo et al , 2020; Nazari et al , 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, another linked limitation of this study concerns the lack of investigation of the internal variables (e.g. strategic governance and operational controls, sustainability control systems, CEOs’ statements or characteristics of the corporate boards), and external variables that can significantly affect the sustainability reporting of firms (Githaiga and Kosgei, 2022; Raimo et al , 2022; Effah et al , 2022; Khan and Sulaiman, 2021; Nursimloo et al , 2020; Nazari et al , 2015).…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with the results of other researchers (Barako and Brown, 2008; Branco et al , 2021; García-Sánchez et al , 2019; Khan et al , 2019) indicating that diverse boards are more likely to improve human rights reporting because their diversities endows them with skills and experiences that facilitate the disclosure of human rights-related information. Khan and Sulaiman (2021) indicated that firms may communicate a picture, say of equal opportunity and gender diversity in their reports, but lacking the details and accuracy of how it has been achieved. Indeed, human rights reporting is based on high quality decisions of the board that are realized when they are diverse.…”
Section: Discussionmentioning
confidence: 99%
“…And so, there is need to incorporate human rights agenda into social responsibility policies. In this sense, the board as the highest governing organ is critical in ensuring that it integrates sustainability and human rights initiatives into its programmes and policies (Khan and Sulaiman, 2021; Rupley et al , 2012). Resource dependence theorists also places a responsibility on corporate boards in the sense that they provide important links with the external environment as well as expertise (Pfeffer and Salancik, 1978) in corporate reporting and in particular ensuring that human rights are upheld.…”
Section: Introductionmentioning
confidence: 99%
“…They proposed that contextual variation across countries such as institutional frameworks or national business system configurations may ultimately influence CSR conceptualization (CSR thinking) and CSR implementation (CSR doing). Their arguments are strongly supported by empirical CSR studies in developing countries, especially in Asia (Khan and Sulaiman, 2021;Choi et al, 2019;Dzever and Gupta, 2012;Kim et al, 2013;Yu et al, 2015). These articles not only suggest that Western values, laws and free-market conditions do not always accord with the Asian context but also show that CSR in Asia has distinctive features due to institutional constellations such as local socio-cultural values and traditions Murphy and Smolarski, 2020;Wang and Juslin, 2009), levels of economic development (Conte et al, 2020;Hong and Kim, 2017) and political system and governance (Rauf et al, 2020;Khan et al, 2018).…”
Section: Introductionmentioning
confidence: 92%